Occupations creating joy for people living with advanced cancer: A qualitative descriptive study. (March 2022) - Bentz, Hannah Holt; Madsen, Stine Hviid; Pilegaard, Marc Sampedro; Østergaard, Lisa Gregersen; Brandt, Åse; Offersen, Sara Marie Hebsgaard; la Cour, Karen
Introduction: For people living with advanced cancer, the possibilities for experiences of joy are seriously influenced by the consequences of the illness. Due to the limited expected lifetime, the need to support such experiences that may entail joy and contribute to quality of life are of importance. Research shows that people with advanced cancer experience quality of life through occupations they are able to perform and enjoy. The aim of this study was to describe which occupations contribute to joy for people living with advanced cancer and explore how they reflect upon these occupations during an occupational therapy intervention. Methods: In total, 111 people with advanced cancer from the intervention group in a randomised controlled trial participated in the present study. Thirty-six of these participants were interviewed, and for 10 participants, this was combined with participant observations. A directed and a conventional content analysis were applied. Results: 148 occupations contributing to joy were categorised into self-care, leisure and productivity. Most occupations were placed into leisure (89%). Participants had three distinct approaches to occupations contributing to joy: Finding solutions to maintain occupations contributing to joy; having an all or nothing approach; and hoping to resume occupations contributing to joy. Conclusion: This study found a wide range of occupations contributing to joy and shows the importance of focusing on enabling leisure occupations for people living with advanced cancer. The wide range of occupations as well as participants' approaches to occupations may be useful to inform future interventions to enable enjoyment for people living with advanced cancer.